2023
DOI: 10.1108/tr-10-2022-0494
|View full text |Cite
|
Sign up to set email alerts
|

Destination competitiveness since 2010: research themes, approaches, and agenda

Abstract: Purpose This study aims to provide a systematic review of the literature on destination competitiveness. It explores research themes and approaches, and outlines an agenda for future research. Design/methodology/approach One hundred and eighty-three journal articles on destination competitiveness published in English since 2010 were collected. Content analysis was performed. Findings The authors found that sustainable development and smart tourism were popular themes related to destination competitiveness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 208 publications
0
4
0
Order By: Relevance
“…Dwyer & Kim (2003) expanded on the idea of destination competitiveness, defining it as the capacity of a place to offer a more pleasurable and unforgettable travel experience in comparison to its rivals. Xu and Au (2023) have pointed out that there has been a growing focus on integrating sustainability concerns into the concept of destination competitiveness in recent years. TDC, according to Dupeyras and MacCallum (2013), is a location's capacity to maximize its appeal to both locals and tourists and to offer clients innovative, high-quality tourism services while ensuring that the resources are managed efficiently and sustainably.…”
Section: Tourism Destination Competitivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Dwyer & Kim (2003) expanded on the idea of destination competitiveness, defining it as the capacity of a place to offer a more pleasurable and unforgettable travel experience in comparison to its rivals. Xu and Au (2023) have pointed out that there has been a growing focus on integrating sustainability concerns into the concept of destination competitiveness in recent years. TDC, according to Dupeyras and MacCallum (2013), is a location's capacity to maximize its appeal to both locals and tourists and to offer clients innovative, high-quality tourism services while ensuring that the resources are managed efficiently and sustainably.…”
Section: Tourism Destination Competitivenessmentioning
confidence: 99%
“…Kunst and Ivandić, (2021) argued that it is not surprising that the tourism industry has become increasingly competitive, with cities, regions, and countries vying for the attention of travelers. Xu & Au (2023) indicated that the COVID-19 pandemic has brought the issue of destination competitiveness to the forefront of research and discussion. Because of this, the tourism sector is faced with challenging issues such as how to draw visitors or welcome them back after the pandemic, how to increase the competitiveness of tourism sites in a sustainable way, and how to market them to different stakeholders in the future (Xu & Au, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental impact-many consumers are concerned about environmental impact and prefer traditional products that are sustainably produced and do not have a negative impact on the environment [50][51][52][53][54].…”
mentioning
confidence: 99%